Bisphenol A Prevents the Synaptogenic Response to Testosterone in the Brain of Adult Male Rats - Leranth, Csaba (The Endocrine Society, 2008)
Exposure measurement data from several developed countries indicate that human beings are widely exposed to low levels of the synthetic xenoestrogen, bisphenol A. We reported previously that bisphenol A, even at doses below the reference safe daily limit for human exposure, recommended by the U.S. Environmental Protection Agency, impairs the synaptogenic response to 17β-estradiol in the hippocampus of ovariectomized rats. Recent experiments revealed that bisphenol A also interferes with androgen receptor-mediated transcriptional activities. Thus, to investigate whether bisphenol A impairs synaptogenesis in the medial prefrontal cortex (mPFC) and hippocampus of adult male rats, castrated and sham-operated animals were treated with different combinations of bisphenol A (300 μg/kg), testosterone propionate (1.5 mg/kg), and sesame oil vehicle. The brains were processed for electron microscopic stereology, and the number of asymmetric spine synapses in the mPFC and CA1 hippocampal area was estimated. In both regions analyzed, bisphenol A reduced the number of spine synapses in sham-operated, gonadally intact animals, which was accompanied by a compensatory increase in astroglia process density. In addition, bisphenol A prevented both the prefrontal and hippocampal synaptogenic response to testosterone supplementation in castrated males. These results demonstrate that bisphenol A interferes with the synaptogenic response to testosterone in the mPFC and hippocampus of adult male rats. Because the hippocampal synaptogenic action of androgens seems to be independent of androgen and estrogen receptors in males, the potential mechanisms that underlie these negative effects of bisphenol A remain the subject of further investigation.